2000
DOI: 10.1055/s-2000-7713
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Sedation for Endoscopic Procedures in Children

Abstract: Propofol sedation for endoscopic procedures is safe and acceptable for children. Propofol sedation should be offered to young children, especially those who express significant anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 13 publications
(14 reference statements)
3
63
0
1
Order By: Relevance
“…We are fully aware that we only measured reported memory, not visual and verbal memory recall, but the results of our study are similar to other evaluating procedural memory after endoscopy [7,9].…”
Section: Strengths and Limitationssupporting
confidence: 88%
See 1 more Smart Citation
“…We are fully aware that we only measured reported memory, not visual and verbal memory recall, but the results of our study are similar to other evaluating procedural memory after endoscopy [7,9].…”
Section: Strengths and Limitationssupporting
confidence: 88%
“…Recently published systematic review on method of sedation and anaesthesia in children showed that PF provide maximal patient comfort with effectiveness comparable to general anaesthesia, in particular, if it is preceded by midazolam premedication [4]. Observational studies performed in children sedated with midazolam showed that approximately 20 % of patients reported some memory of the EGD whereas anaesthesia with propofol resulted in loss of procedural memory in almost all patients [1,7,9]. One of these studies also showed that anaesthesia with PF was associated with the need for restraint in only 3 % of cases, compared with 57 % in the midazolam group which is similar to our trial.…”
Section: Comparison To Other Studiesmentioning
confidence: 99%
“…With growing evidence supporting its use in both adults and children [16, 17, 18, 19, 20, 21, 22, 23]propofol now stands at the threshold of a broad introduction into the endoscopy suite. Today, three major questions regarding its use have to be answered:…”
Section: Introductionmentioning
confidence: 99%
“…Other goals are to maximize efficiency and contain costs [49]. The method of sedation is a matter of choice after careful consideration of a number of factors including the patient's condition, ASA classification, the type of procedure, the parents' and patient's preference, and the level of cooperation of the patientWith proper patient selection, intravenous sedation is a safe and effective method for sedation in pediatric endoscopy [50,51]. General anesthesia should be considered necessary for highly complicated procedures and for patients at high risk for cardiovascular complications.…”
Section: Pediatric Endoscopymentioning
confidence: 99%